Plastic surgery. - Neligan, Peter; Song, David H.; Van Beek, Allen (Elsevier Saunders, 2013)
Provides you with the knowledge and techniques across your entire field, allowing you to offer every patient the best possible outcome. This title helps you to overcome any challenge you may face and exceed your patients' expectations.